Admission Heart Rate Predicts Poor Outcomes in Acute Intracerebral Hemorrhage: The Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial Studies. Issue 6 (June 2016) - Qiu, Miaoyan; Sato, Shoichiro; Zheng, Danni; Wang, Xia; Carcel, Cheryl; Hirakawa, Yoichiro; Sandset, Else C.; Delcourt, Candice; Arima, Hisatomi; Wang, Jiguang; Chalmers, John; Anderson, Craig S.
Abstract : Background and Purpose—: Faster heart rate predicts higher mortality in coronary heart disease and acute ischemic stroke, but its prognostic significance in intracerebral hemorrhage remains uncertain. We aimed to determine the effect of admission heart rate on clinical and imaging outcomes in patients with intracerebral hemorrhage. Methods—: A post hoc pooled analysis of the pilot and main phases of the Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial (INTERACT 1 and 2). Clinical outcomes were mortality and modified Rankin Scale score at 90 days; and imaging outcome was absolute growth in hematoma volume during the initial 24 hours. Patients were divided into 4 categories according to baseline heart rate (<65, 65–74, 75–84, and ≥85 bpm) and analyzed using multivariable adjusted models with the lowest heart rate group as the reference. Results—: Of 3185 patients with available data, higher admission heart rate was associated with both mortality and worse modified Rankin Scale score: adjusted hazard ratio for heart rate (≥85 versus <65 bpm) 1.50 (95% confidence interval, 1.07–2.11) and adjusted odds ratio 1.33 (95% confidence interval, 1.08–1.63), respectively (both P -trend <0.05). There was no significant relationship between heart rate and absolute growth in hematoma volume ( P -trend, 0.196). Conclusions—: Higher admission heart rate is independently associated with death and poor functional outcome after acute intracerebral hemorrhage. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00226096 and NCT00716079. Abstract : Supplemental Digital Content is available in the text.